2018
DOI: 10.1093/mnras/sty247
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV MaNGA: the spatial distribution of star formation and its dependence on mass, structure, and environment

Abstract: We study the spatially resolved star formation of 1494 galaxies in the SDSSIV-MaNGA Survey. SFRs are calculated using a two-step process, using H α in star forming regions and D n 4000 in regions identified as AGN/LI(N)ER or lineless. The roles of secular and environmental quenching processes are investigated by studying the dependence of the radial profiles of specific star formation rate on stellar mass, galaxy structure and environment. We report on the existence of 'Centrally Suppressed' galaxies, which ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
60
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 109 publications
(156 reference statements)
13
60
3
2
Order By: Relevance
“…This agrees with the low levels of star formation found in many early-type galaxies using UV-optical colours (Yi et al 2005;Kaviraj et al 2007aKaviraj et al , 2008Schawinski et al 2007), which has been attributed to minor mergers (Kaviraj et al 2009). Our results are consistent with Spindler et al (2018) who examined the SSFR radial profiles as a function of stellar mass, Sérsic index and central velocity dispersion. They found that intermediate and high mass galaxies with high velocity dispersion or Sérsic index (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with the low levels of star formation found in many early-type galaxies using UV-optical colours (Yi et al 2005;Kaviraj et al 2007aKaviraj et al , 2008Schawinski et al 2007), which has been attributed to minor mergers (Kaviraj et al 2009). Our results are consistent with Spindler et al (2018) who examined the SSFR radial profiles as a function of stellar mass, Sérsic index and central velocity dispersion. They found that intermediate and high mass galaxies with high velocity dispersion or Sérsic index (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Again using MaNGA data, Wang et al (2018) found evidence for strong gradients in spectral indices, indicating insideout growth in massive galaxies (M * > 10 10 M ), but flat gradients in lower mass galaxies. Finally, Spindler et al (2018) measured the SSFR profiles of intermediate and high mass MaNGA galaxies and found that galaxies with high velocity dispersion or Sérsic index (i.e. significant bulges) had centrally suppressed starformation.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is in agreement with numbers of observational evidences (e.g. Prantzos & Boissier 2000;Gogarten et al 2010;Spindler et al 2018). Indeed, a natural consequence of inside-out growth is that central regions of galactic discs are, on average, older and more metal-rich than the outskirts (e.g.…”
supporting
confidence: 91%
“…The average profile of QG galaxies shows a slow decline towards large radii. As shown in the central panel of Figure 15, the average SFR surface density of the SFs has an exponential profile, and its linear fit shows a slope of −0.67 (consistent with Spindler et al 2018). Instead, the average trend of QGs shows suppression of SFR with respect to the exponential trend of SFs, with a linear fit characterised by a slope of −0.43.…”
Section: The Average σSfr Radial Profilesupporting
confidence: 56%
“…Analyzing a small sample of galaxies in the MaNGA prototype run (P-MaNGA), Li et al (2015) classified the radial profiles of their three diagnostic parameters (Dn4000), EW(Hδ), and EW(Hα)) as either 'centrally quiescent' or 'centrally star forming'. Recently, Spindler et al (2018) investigated the spatial distribution of star formation in a large sample of galaxies of the MaNGA survey (Bundy et al 2015), revealing the existence of two groups of galaxies, which they named 'Centrally Suppressed' and 'Unsuppressed' regarding the radial distribution of their specific star formation rates. Analogously, Medling et al (2018) studied the resolved star formation of a sample of galaxies in the SAMI survey, also finding a split between galaxy populations with centrally concentrated star formation and those with flatter star formation profiles.…”
Section: Introductionmentioning
confidence: 99%